Analysis of Revenues, Costs and Average Costs of Highway Concessions in Chile - Alfaro-Marchant, M; Sepulveda-Rojas, J (Elsevier Ltd, 2020)
In this document we present an analysis of the revenues generated, the total costs and average costs incurred by Chile s highway concessionaires between the years of 1995 and 2014. We have collected financial data from the Chilean Assets and Insurances Authority s website, and with this data, we have determined that the highway concessions system (as a whole) generated revenues of around 25,137 million dollars and incurred total costs of 21,193 million dollars during this period. Therefore, they have gained a profit of 3944 million dollars. Moreover, the accumulated investment by 2014 was approximately 12,000 million dollars and, therefore, the capital revenue was 26%. However, since the concessionaires capital structure, in general, considers 20% as equity and 80% as debt, then the equity s return rate could have been over 100%. Additionally, we estimated the average costs (unitary costs), and found that this industry presents natural monopoly characteristics because its average cost decreases as vehicle flow increases. Furthermore, we compared the average costs of main concessionaires with their weighted average fares and discovered that some of fares are over valuated between 30 and 330%. © 2019 Elsevier Ltd